Social Networks in the Jewelry Industry: A Qualitative Research on Ethnic/Minority Entrepreneurs in Turki̇ye - Arıkboğa, Fatma Şebnem; DEVECİYAN, MERİ TAKSİ (Beykoz Üniversitesi, 2024)
The study aims to reveal how minority entrepreneurs benefit from social networks and the role of social networks in the jewelry sector, which is considered one of the sectors where the use of social networks can be easily detected, where ethnic and minority entrepreneurs are clustered in Istanbul province, in Türkiye. In this context, phenomenology design was used as a qualitative research method, and the research data was collected through individual face-to-face in-depth interviews with a pre-prepared semi-structured questionnaire with 24 minority entrepreneurs registered with the Istanbul Chamber of Jewelers (IKO) and the Istanbul Chamber of Commerce Jewelry Committee (ITO). Descriptive and coding-based qualitative content analysis was used to analyze the data. MAXQDA qualitative data analysis program was used to visualize the data. As a result of the study, minority entrepreneurs in the jewelry sector benefit heavily from their social networks (especially their co-ethnic group) to access resources. Within the framework of the unique structure of the jewelry sector and the internal dynamics of minorities, the impact of the concept of "master" on the social networks of entrepreneurs in addition to family friends, who are among their strong and close networks, was also observed. The study is expected to contribute to the field by offering suggestions, as it is the only study that addresses the concept of "master" in the sectors of the creative industries and brings the concept to the literature.
Kuyumculuk Sektöründe Sosyal Ağlar: Türkiye’deki Etnik/Azınlık Girişimciler Üzerine Nitel Bir Araştırma
Keywords: Ethnic Entrepreneurship; Minority Entrepreneurship; Social Networks; Social Network Theory; Master